El arroz y su medio ambiente - Vargas, José Patricio (International Center for Tropical Agriculture, 2010)
Rice and its environment The different environmental factors that influence rice production are analyzed, including: temperature (high, critical low, water, and air); solar radiation; solar energy and photosynthesis; water; precipitation; transpiration; water/soil ratio; wind; and relative humidity. In brief, the response of the rice plant to diverse climatic factors and environmental conditions determines, to a great extent, the speed and intensity of metabolic processes controlled by the plant’s genetic code. The better these processes are expressed, the higher the production level and productivity of plants in terms of economic performance.